2018
DOI: 10.1002/jrs.5488
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics study of cubic Tb2O3

Abstract: We report a joint experimental and theoretical study of the lattice dynamics of cubic Tb2O3. Up to 16 optical Raman‐active modes have been observed with polarized and unpolarized Raman scattering measurements on a high‐quality Tb2O3 single crystal. The measured wavenumbers have been compared with those of other rare‐earth (RE) and related sesquioxides with cubic (C‐type or bixbyite) structure. First‐principles calculations have allowed us to assign the symmetry of the experimentally observed Raman‐active modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
0
11
0
2
Order By: Relevance
“…In contrast, PBEsol seems to be in better agreement for the high-wavenumber modes (>250 cm –1 ). While PBEsol clearly underestimates the unit-cell volume of both the C-, B-, and A-type phases of Tb 2 O 3 , the reduced interatomic distances predicted in this case seem to yield increased spring constants and therefore improved results in the case of the high-wavenumber modes (with mainly O vibrations as shown in ref ( 89 )). From now on, we rely on the GGA-PBE vibrational results as this functional better reproduces both the compression behavior of the unit-cell volume and the low-wavenumber modes (with mainly Tb vibrations).…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…In contrast, PBEsol seems to be in better agreement for the high-wavenumber modes (>250 cm –1 ). While PBEsol clearly underestimates the unit-cell volume of both the C-, B-, and A-type phases of Tb 2 O 3 , the reduced interatomic distances predicted in this case seem to yield increased spring constants and therefore improved results in the case of the high-wavenumber modes (with mainly O vibrations as shown in ref ( 89 )). From now on, we rely on the GGA-PBE vibrational results as this functional better reproduces both the compression behavior of the unit-cell volume and the low-wavenumber modes (with mainly Tb vibrations).…”
Section: Resultsmentioning
confidence: 59%
“…We have recently characterized the Raman-active modes of C-type Tb 2 O 3 at room pressure. 89 In the present work, we have performed unpolarized RS measurements and observed up to 16 out of 22 Raman-active modes of the cubic phase as a function of pressure (see Figure 11 ). It can be observed that the cubic phase is stable from 0 to 6.8 GPa and has completely disappeared at 7.5 GPa.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations